Analisis Penyebab Kesulitan Membaca pada Siswa Kelas IV Sekolah Dasar: Analysis of the Causes of Reading Difficulties in Grade IV Elementary School Students - Rahmawati Rahmawati; Syarifah Nur Fajrin; Nasaruddin Nasaruddin (Al-Musannif, 2024)
The phenomenon of reading difficulties in upper elementary school students needs a solution. Moreover, the upper elementary school curriculum contains theories and concepts that require students' good reading skills. This study aims to analyze the types, causes, and impacts of reading difficulties in fourth-grade elementary school students. This qualitative study uses a phenomenological approach. Primary data consists of teachers and five fourth-grade students who have reading difficulties. Secondary data are journals and books as a theoretical basis. Data were collected through observation, interviews, and documentation, then analyzed using qualitative analysis techniques. The results of the study showed (1) the types of students' reading difficulties are not recognizing letters, not being able to identify words, not being fluent in reading aloud, not understanding the meaning of the text, and not being able to listen to reading, (2) The factors causing students' reading difficulties are family factors, lack of interest and motivation to read, and students' intelligence levels. (3) The reading difficulties experienced by students have a significant impact on students' academic, psychological, and social interactions. This study has implications for the importance of teachers understanding the characteristics of students in "reading" learning. This understanding greatly determines the direction of learning related to methods, strategies, techniques, tactics, and teaching styles.